Comparison of multi-carriers based PWM for multilevel converters - Mohammed, B.S. (Praise Worthy Prize S.r.l, 2014)
This paper addresses a comparative study of modulation techniques used for multilevel converters and aims to present a new multi-carrier pulse width modulation (PWM) technique called wave shift multi-carrier PWM (WSPWM). The proposed switching technique generated lower voltage total harmonic distortion (THD) as compared to the conventional multicarrier based PWM schemes such as phase-shift PWM (PSPWM), level-shift PWM (LSPWM), switching frequency optimal PWM (SFPWM) and selective harmonic elimination technique (SHET). To compare the performance of the proposed method with PSPWM, LSPWM, SFPWM and SHET techniques, three-phase five, seven, nine and eleven-level circuit topologies of cascade multilevel converter (CMC) were designed and simulated. Based on the seven-level CMC topology the dynamic behavior of both shunt and series active power filters were investigated for power quality improvement of a single feeder distribution system. Digital simulations were carried out using the well-developed industry standard power system program, PSCAD/EMTDC to validate the performance of CMC based shunt and series active power filters. Â© 2014 Praise Worthy Prize S.r.l.-All rights reserved.